2023
DOI: 10.1186/s13071-022-05554-7
|View full text |Cite
|
Sign up to set email alerts
|

A new WHO bottle bioassay method to assess the susceptibility of mosquito vectors to public health insecticides: results from a WHO-coordinated multi-centre study

Abstract: Background The continued spread of insecticide resistance in mosquito vectors of malaria and arboviral diseases may lead to operational failure of insecticide-based interventions if resistance is not monitored and managed efficiently. This study aimed to develop and validate a new WHO glass bottle bioassay method as an alternative to the WHO standard insecticide tube test to monitor mosquito susceptibility to new public health insecticides with particular modes of action, physical properties or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 15 publications
1
33
0
Order By: Relevance
“…Our control experiments where female adults were exposed to linseed oil soap alone allowed us to rule out the possibility that this surfactant on its own had lethal effects on mosquitoes. Corbel et al [14] have also demonstrated Mero®, a formulation of rapeseed fatty acid esters had no insecticidal activity on Anopheles mosquitoes. Using estimates of 24-h LC50 and LC99, we then found that blends of clothianidin and linseed oil soap are highly potent leading to a drastic increase in shortterm lethal toxicity of the active ingredient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our control experiments where female adults were exposed to linseed oil soap alone allowed us to rule out the possibility that this surfactant on its own had lethal effects on mosquitoes. Corbel et al [14] have also demonstrated Mero®, a formulation of rapeseed fatty acid esters had no insecticidal activity on Anopheles mosquitoes. Using estimates of 24-h LC50 and LC99, we then found that blends of clothianidin and linseed oil soap are highly potent leading to a drastic increase in shortterm lethal toxicity of the active ingredient.…”
Section: Discussionmentioning
confidence: 99%
“…The standard operating procedure for testing the susceptibility of adult mosquitoes recommends using Mero® as surfactant when exposing Anopheles and Aedes populations to neonicotinoids and butenolides [4,14]. A large-scale study conducted to test the efficacy of broflanilide, a new meta-diamide insecticide, on several Anopheles laboratory colonies from different African countries has noted a drastic increase in toxicity of the active ingredient due (which was not certified by peer review) is the author/funder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It might be appropriate to revisit the diagnostic dose as the longer the observation time, the more other factors could affect the mortality rate. Furthermore, an alternative WHO bottle bioassay recently described by Corbel et al [ 37 ] could also be considered for evaluating the susceptibility of Anopheles vectors to clothianidin.…”
Section: Discussionmentioning
confidence: 99%
“…coluzzii Ngousso) in order to determine LC50 and LC99 corresponding to the lowest concentrations required to kill respectively 50% and 99% of susceptible mosquitoes. After 1 h exposure to the insecticide, lethal concentrations were determined within 24 h and 72 h. By contrast to clothianidin whose toxicity has been tested with at least one susceptible strain 7,11,28,29 , there is no information on the lethal concentrations of acetamiprid, imidacloprid and thiamethoxam to African malaria mosquitoes. Therefore, we focused primarily on those three active ingredients.…”
Section: Lethal Concentrations Determinationmentioning
confidence: 99%